What is the role of the oral and maxillofacial department in the preoperative management of patients awaiting cardiac operations?. Issue 5 (May 2015) - Jenkins, G.W.; Holmes, A.; Colman-Nally, J.; Mustafa, S.
Abstract There is limited evidence and guidance on best practice regarding preoperative dental assessments of patients awaiting cardiac operations. To analyse current practice in oral and maxillofacial units across the United Kingdom, we did a telephone survey to find out how these patients are managed. All maxillofacial departments in the United Kingdom were contacted, with a response rate of 77%. Those attached to dental schools were excluded. Most departments did extractions only, and in many, patients were assessed and treated within 7 days of being referred, although this varied. Most units did not offer antibiotic prophylaxis to patients at high risk of infective endocarditis, but some did after advice had been sought from a cardiologist. Respondents in 76% thought that preoperative dental assessments for cardiac patients were an appropriate use of resources. We propose a more integrated pathway for the management of these patients (particularly considering the pressure on time for treatment) that focuses primary and secondary resources accordingly.